The effect of carbon nanoparticles staining on lymph node tracking in colorectal cancer: A propensity score matching analysis - Liu, Fei; Peng, Dong; Liu, Xiao-Yu; Liu, Xu-Rui; Li, Zi-Wei; Wei, Zheng-Qiang; Wang, Chun-Yi (Frontiers in Surgery, 2023)
Purpose The aim of this study was to evaluate the effect of carbon nanoparticles staining (CNS) on colorectal cancer (CRC) surgery, lymph node tracing and postoperative complications using propensity score matching (PSM). Method Patients who were diagnosed with CRC and underwent surgery were retrospectively collected from a single clinical center from Jan 2011 to Dec 2021. Baseline characteristics, surgical information and postoperative information were compared between the CNS group and the non-CNS group. PSM was used to eliminate bias. Results A total of 6,886 patients were enrolled for retrospective analysis. There were 2,078 (30.2%) patients in the CNS group and 4,808 (69.8%) patients in the non-CNS group. After using 1: 1 ratio PSM to eliminate bias, there were 2,045 patients left in each group. Meanwhile, all of their baseline characteristics were well matched and there was no statistical significance between the two groups (P > 0.05). In terms of surgical information and short-term outcomes, the CNS group had less intraoperative blood loss (P < 0.01), shorter operation time (P < 0.01), shorter postoperative hospital stay (P < 0.01), less metastatic lymph nodes (P = 0.013), more total retrieved lymph nodes (P < 0.01), more lymphatic fistula (P = 0.011) and less postoperative overall complications (P < 0.01) than the non-CNS group before PSM. After PSM, the CNS group had less intraoperative blood loss (P = 0.004), shorter postoperative hospital stay (P < 0.01) and more total retrieved lymph nodes (P < 0.01) than the non-CNS group. No statistical difference was found in other outcomes (P > 0.05). Conclusion Preoperative CNS could help the surgeons detect more lymph nodes, thus better determining the patient's N stage. Furthermore, it could reduce intraoperative blood loss and reduce the hospital stay.